Breast feeding and the weekend effect: an observational study. Issue 7 (8th July 2016) - Fitzsimons, Emla; Vera-Hernández, Marcos
Abstract : Objective: To compare the incidence of breast feeding by day of week of birth. Design: Retrospective database study using 16 508 records from the 2005 and 2010 Infant Feeding Surveys. Setting: England and Wales, UK. Participants: Mothers of a sample of births from among all registered births in the periods August–September 2005 and August–October 2010. Main outcome measure: Incidence of breast feeding after birth. Results: Among babies of mothers who left full-time education aged 16 or under, the incidence of breast feeding was 6.7 percentage points lower (95% CI 1.4 to 12.1 percentage points) for those born on Saturdays than for those born on Mondays–Thursdays. No such differences by day of week of birth were observed among babies of mothers who left school aged 17 or over. Conclusions: Breastfeeding policy should take into account differences in breast feeding by day of week of birth, which are apparent among low-educated mothers. Further research is needed to ascertain the reason for this finding.